2018
DOI: 10.1111/1440-1681.12994
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in patients with recurrent endometrial polyps could exacerbate Th17 responses

Abstract: Endometrial polyps (EPs) are outgrowths in the endometrium with unknown etiology. The fact that EPs can often recur after surgical removal suggests that EPs are not induced by random events but by continuous or recurrent processes in patients. We previously demonstrated that the risk of EP development was positively associated with overactive Th17 responses. However, the requirements of Th17 upregulation are yet unclear. Here, we recruited 26 women with symptomatic EP and 24 without EP, and peripheral mononucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…The difference in hormone levels between the two groups was significant with p >0.001, which shows a significant difference in the AMH level of the two groups. Other studies have concluded that AMH and PCOS can be a good differentiator between endometrial polyp sufferers and non-affected people (16,19). As in this research, a clear difference was seen between the level of this hormone in endometrial polyp and healthy subjects.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The difference in hormone levels between the two groups was significant with p >0.001, which shows a significant difference in the AMH level of the two groups. Other studies have concluded that AMH and PCOS can be a good differentiator between endometrial polyp sufferers and non-affected people (16,19). As in this research, a clear difference was seen between the level of this hormone in endometrial polyp and healthy subjects.…”
Section: Discussionsupporting
confidence: 70%
“…Although the serum AMH level cannot accurately predict the risk level of endometrial polyps in women with PCOS, different studies have found different threshold levels (from AMH 3.8 to 5 ng/cc) to be sensitive for diagnosis (16,19,20). In a study conducted by Munro (20) on 60 PCOS cases and a control group, there was a significant difference in the average AMH level in patients with 14.7 and 3.14 in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Although reproductive immunology has achieved great progresses over past decades ( 14 16 ), and the view “immune suppression” during pregnancy has been widely accepted as one of important conceptions in the field of reproductive immunology ( 15 , 16 ), further insights into immunity features of women of reproductive-age still remains to be fully illuminated. Although previous study showed that various immune cells, including natural killer (NK) cells ( 17 ), macrophages ( 9 ), and CD4 + T cells ( 18 ), play key roles in maintaining normal pregnancy at term, however, how peripheral immunity affects pregnancy ability is yet to be fully understood. Therefore, in this prospective study, we focused on characterizing immune profiles/phenotypes of circulating immune cells, such as CD4 + T cells, CD8 + T cells, NK cells, and γδ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Black et al (2013) reported that inflammatory lesion associated with infiltrated mast cells in EP tissue plays important roles in inducing local immune disturbances (8). Moreover, the circulating monocytes of EP patients can secrete high levels of TNF, IL-1b, IL-6, and IL-23, which could impair fertility (9). In addition, endometrial inflammation (10,11) or infection of chlamydia trachomatis (12) are also prone to induce AUB and subfertility (10).…”
Section: Introductionmentioning
confidence: 99%
“…Исходя из результатов нашего исследования, можно заметить такой факт, что количество моноцитов в периферической крови при сочетании эндометриоза с другими патологиями женской репродуктивной системы (в том числе заболеваниями эндометрия) было значимо выше. Роль макрофагов в становлении патологии эндометрия активно обсуждается исследователями, которые показывают патогенетическую значимость этой клеточной популяции при полипах эндометрия, гиперплазии эндометрия и других заболеваниях [6,7]. Интересно, что для возникновения маточно-перитонеального рефлюкса имеются некоторые факторы риска, среди которых упоминаются различные заболевания женской репродуктивной системы [8].…”
Section: Discussionunclassified